Dupilumab for Chronic Prurigo in Different Backgrounds: A Case Series - Luo N; Wang Q; Lei M; Li T; Hao P (Dove Medical Press, 2022)
Nana Luo,1,2 Qiuyue Wang,2 Min Lei,2 Tianhao Li,1 Pingsheng Hao1 1Department of Dermatology, Hospital of Chengdu University of Traditional Chinese Medicine, Chengdu, People's Republic of China; 2School of Clinical Medicine, Chengdu University of Traditional Chinese Medicine, Chengdu, People's Republic of ChinaCorrespondence: Tianhao Li; Pingsheng Hao, Hospital of Chengdu University of Traditional Chinese Medicine, No. 39 Shi-er-qiao Road, Chengdu, People's Republic of China, Tel +86-13880986337 ; +86-13881965024, Fax +86-28-87732407, Email litianhao_doctor@163.com; hpswl@126.comAbstract: Chronic prurigo (CPG) is a chronic inflammatory disease characterized by intense pruritus, and therapy is often challenging due to its unclear pathogenesis. Here, we report four patients with refractory CPG from different backgrounds who experienced failure of conventional therapy and were controlled with dupilumab, accompanied by a significant decrease in pruritus numerical rating scale, dermatology life quality index, and investigator global assessment, without adverse effects. Furthermore, dupilumab improved the condition of asthma in CPG patients along with an increase in asthma control test scores.Keywords: dupilumab, chronic prurigo, therapy, asthma